Nutrient absorption and enzyme activity of Persian oak (Quercus brantii) seedlings under ectomycorrhizal fungi - Elham Malekzadeh; Behnaz Yousefshahi; Mohsen Olamaee; Nasim Ghalavand (BMC Plant Biology)
Abstract This study aimed to investigate the influence of ectomycorrhizal fungi on nutrient uptake and the activity of the enzymes alkaline phosphatase and urease under pot conditions. In the experiment, seedlings of Persian oak (Quercus brantii) were inoculated with four species of ectomycorrhizal fungi (Amanita crocea, Boletus comptus, Inocybe rimosa, and Tricholoma giganteum) in three replicates. After seven months in a greenhouse with controlled humidity, various parameters were examined, including leaf dry weight, the percentage of root colonization, nutrient concentration and uptake (N, P, Ca, Mg, Zn, Fe, and Cu), and enzyme activity. The results showed that all types of ectomycorrhizal fungi contributed to an increase in leaf dry weight, nutrient concentration, and uptake of N, P, K, Ca, Mg, Zn, Fe, and Cu in Persian oak seedlings compared to the control group. The treatments also showed differences in root colonization, with Boletus comptus showing the highest percentage (87%). In particular, Inocybe rimosa and Tricholoma giganteum showed significant success in improving nutrient uptake and the activity of the enzymes urease and alkaline phosphatase. The study suggests that the potential of these ectomycorrhizal fungi, especially Inocybe rimosa and Tricholoma giganteum, can be utilized for the establishment of Persian oak seedlings and support the regeneration of forests affected by oak blight disease.